Isolated superior mesenteric artery dissection: An unusual presentation quashed by an unusual approach - Ullah, Waqas; Mehmood, Asif; Hamid, Mohsin; Mukhtar, Maryam; Khan, Muhammad Atique Alam (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Ullah W, Mehmood A, Hamid M, Mukhtar M, Khan MAA. Isolated superior mesenteric artery dissection: An unusual presentation quashed by an unusual approach. Turk J Gastroenterol 2019; 30(7): 648-51.